African American Satisfaction With the SNAP-Ed Program: A Qualitative Exploration. (14th June 2022) - Greene, Matthew; Briley, Chiquita; Williams, Shakera; Freightman, Jamila; Holston, Denise
Abstract: Objectives: Nutrition educators and public health professionals are increasingly focused on structural racism and its contribution to racial disparities in rates of food insecurity and obesity. In the context of these barriers to healthful eating affecting marginalized populations, nutrition education programs must be carefully evaluated to determine whether they meet the needs of those populations. This study aimed to assess African Americans perceptions of and satisfaction with the SNAP-Ed program in Louisiana. Methods: Three trained African American facilitators conducted five focus group discussions (FGD) with 25 African American participants in SNAP-Ed. The discussion guide for FGD was based on issues identified by SNAP-Ed leadership in Louisiana and revised by African American implementers of SNAP-Ed. FGD were recorded and transcribed verbatim. Transcripts were coded independently using inductive and in-vivo coding by two members of the research team using Dedoose software. Results: Participants were generally satisfied with the program and thought information was important for African Americans in the context of medical issues faced by their community. However, participants viewed lessons as race neutral and thought they should include more information about African American history and culture. Participants also noted a lack of engagement with the African American stressed the need for African American staff to better engage with the African American community. Conclusions: The SNAP-Ed program in Louisiana may need to be modified to specifically address African American food history and culture. The implementation of the program should be modified to include more African American SNAP-Ed staff and better engage with the African American community. Funding Sources: SNAP-Ed.